Determininants of Diarrhea-Related Health Care Seeking Behavior among Indonesian Mothers with Under-five Children during the COVID-19 Pandemic - Asril, Nice Maylani; Pasek, Made Suadnyani; Tirtayani, Luh Ayu; Agustini, Ni Nyoman Mestri; Wahyuni, Ni Putu Dewi Sri; Mahayanti, Ni Wayan Surya (Journal of Ecohumanism, 2024)
This study investigated factors influencing healthcare-seeking behaviours of Indonesian mothers during the COVID-19 pandemic when their children had diarrhea. The 117 participants completed a self-report which measured the socio-demographic condition, knowledge about diarrhea, illness perception, anxiety, and health care seeking behavior for diarrhea. The data were analyzed with the descriptive statistics, Chi-square, and logistic multinomial regression analysis. Analysis revealed critical determinants including child age, maternal occupation, education, transportation, knowledge of diarrhea, and illness perception. The model accurately predicted 84.6% of healthcare-seeking behaviours, with mothers favoring formal care for younger children and education positively influencing formal healthcare utilization. The type of public transportation significantly influenced healthcare-seeking behavior. While accurate knowledge of diarrhea increased professional care seeking, the model explained only 5.61% of behavior variation, suggesting unexplored factors. Addressing these factors could improve child health outcomes during pandemics. Policy enhancements and cultural sensitivity in health education are vital for efficacy. Deepening understanding and developing effective interventions amidst pandemics require further research.